2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28286
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Motivations for High-Interest Students

Abstract: As the call to increase entrepreneurial training within academic engineering institutions increases, understanding the target audience and its motivations becomes increasingly important. This qualitative research study provides insight into the backgrounds and motivations of engineering students who exhibited high entrepreneurial interest during their sophomore or junior year. Students taking a Technical Communication for Engineers course were given a series of entrepreneurial interest questions. Those student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One paper exploring students' motivations to study engineering found that students with a high entrepreneurial interest mentioned grit (persistence) as being a core attribute to excel in engineering (Call et al 2017). Finally, one paper presented an alternative definition of grit because participants' perceptions of problem solving suggested that grit is domain-and task-specific, and also related to short-term motivation (Kirn and Benson 2018).…”
Section: Qualitative Approaches To Gritmentioning
confidence: 99%
“…One paper exploring students' motivations to study engineering found that students with a high entrepreneurial interest mentioned grit (persistence) as being a core attribute to excel in engineering (Call et al 2017). Finally, one paper presented an alternative definition of grit because participants' perceptions of problem solving suggested that grit is domain-and task-specific, and also related to short-term motivation (Kirn and Benson 2018).…”
Section: Qualitative Approaches To Gritmentioning
confidence: 99%